PENCITRAAN POLITIKUS MILENIAL DI MEDIA SOSIAL PERSPEKTIF HUKUM KOMUNIKASI ISLAM - Muhammad Qadaruddin Abdullah; Muhammad Shuhufi; Dinul Fitrah Mubaraq; Fatmawati Hilal (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2020)
The purpose of this research is to find out how regent candidate pairs build self-image through programs and policies that can attract voters' attention and increase voter presentation and how to deliver messages. This research uses a descriptive qualitative methodology, analyzes the messages of candidate pairs delivered on social media, then analyzes them using Islamic communication. that the regent's candidate pair had compiled a program that was by the voter segment. The delivery of the program was carried out through social media including Facebook, Instagram, YouTube, website, the messages conveyed could be seen in the media center which collected all the messages conveyed, but the messages that have not been submitted in detail. In delivering messages, candidate pairs of regents use a pragmatic approach by making programs related to voter needs. Candidate pairs also use a rational approach by conveying messages rhetorically and rationally.